Penguatan Literasi Keuangan untuk Ketahanan Keluarga pada Kelompok Perempuan Muslim Pra Sejahtera: Strengthening Financial Literacy for Family Security on Pre Prosperous Women Muslim Group - Salju Salju; Hadi Pajarianto; Muhammad Yusuf; Imam Pribadi; Duriani Duriani; Ibrahim Halim; Goso Goso (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Knowledge, skills, and confidence in financial management for women are essential given the complexity of their more frequent role in managing financial resources in a family. The implementation of community service aims to increase the financial resilience of pre-prosperous women's families through increased financial literacy in Palopo City. The approach to implementing community service uses the Sustainable Livelihood Approach (SLA), which is oriented toward the sustainability of the family economy so that the family is stronger. The results of the pre-test implementation confirmed that the participants' level of financial proficiency was shallow. With financial literacy counseling and simulated treatment of financial management on family financial decisions related to skills taking into account the 5M (controlling, spending, building, setting aside, and developing), there was a significant increase in proficiency in financial management in the post-test evaluation carried out by the team. In these results, there is an increase in knowledge, skills, and commitment to improving financial literacy and good behavior so that family financial resilience increases.